T.W. - Self-Portraits of the Playwright: Tennessee Williams’s Paintings, Poetics, Prose - John S. BAK (E-REA)
In the summer of 1939, Tom “Tennessee” Williams painted his first of several self-portraits. The year is significant because it also marked his entrance into the New York theatre world. Though there was little question that Williams would become a playwright, he never abandoned his painting entirely – or his obsession with self-portraiture. For Williams, traces of his lived experiences can be found in nearly every one of his works, textual and graphic alike. Drawing on Barthes’s theory of the (auto)biographeme and Hall’s sociological study of the self-portrait, this article studies that first graphic self-portrait alongside the many textual self-portraits (memoirs, essays, letters and private notebook entries) that Williams produced in or about 1939 in the aim of demonstrating how, in complementing each other, the graphic and the textual self-portraits document his transformation from Tom into Tennessee.